N‐Glycosylation analysis of formalin fixed paraffin embedded samples by capillary electrophoresis. Issue 17 (11th December 2015) - Donczo, Boglarka; Szigeti, Marton; Ostoros, Gyorgyi; Gacs, Alexandra; Tovari, Jozsef; Guttman, Andras
Abstract : In this study, N‐linked glycans from intact, formalin treated and formalin fixed paraffin embedded (FFPE) standard glycoproteins, human serum and mouse tumor tissue samples were investigated in respect to their susceptibility for formaldehyde treatment mediated changes. FFPE samples were first deparaffinized, followed by solubilization in radioimmunoprecipitation assay buffer and treated with PNGase F for N‐glycan release. The released glycans were labeled with a charged fluorophore and analyzed by capillary electrophoresis with laser induced fluorescent detection. No significant alterations were found in the N‐glycome profile at any of the investigated complexation levels (i.e., glycoprotein, serum and tissue samples) of the study. These results suggest that FFPE samples can be readily used for global N‐glycome analysis holding the promise to find novel carbohydrate biomarkers in prospective and retrospective studies. Exoglycosidase based carbohydrate sequencing was also applied to reveal some basic structural information about the N‐linked carbohydrates of the mouse tumor tissue samples.